The Impact of Covid-19 to Mcdonald’s: Its Response and Post-Pandemic Plan - editor aibpm; Lee Hui Yennie Chong; Xinyi Yang; Yang Wei; Yifan Wang; Talal A M A Alzufairi; Reem Meshal R A Aljuwaisri (Advances in Global Economics and Business Journal, 2022)
Under the influence of Covid-19, most countries fell into a severe economic crisis. As the world's greatest restaurant chain, McDonald's has adopted measures such as simplified menus and contactless services to overcome this situation. This study aims to investigate the impact of Covid-19 on McDonald’s. We used the method of collecting literature to investigate. More data and facts were achieved from the Internet access and reviewing various researchers’ case studies, studies, and journals. Besides, this research explains McDonald's response to Covid-19 and plans to control the situation after the pandemic. Through this survey, we can understand the impact of McDonald’s strategy, and analyze what plan McDonald’s will adopt after the epidemic to increase customer trust, attract consumers, and improve operations performance.